University Students' Awareness of the Concept of National Belonging: A Study on its Scope and Depth - Saleh, Shoeb; AlAli, Rommel (Journal of Ecohumanism, 2024)
The research underscores the crucial role that Jordanian universities, particularly Yarmouk University, play in fostering national belonging among students. It aimed to assess students' awareness of national belonging and to inform decision-makers at Yarmouk University about the current state of this awareness and its various dimensions. The findings indicate a generally weak understanding among the study sample regarding the concept of national belonging and its associated priorities, elements, and connections to other concepts. More than three-quarters of respondents acknowledged the need for community institutions to actively promote national belonging. The study also identified several factors contributing to diminished national belonging, such as economic and social pressures, tribal fanaticism, and favoritism. Additionally, there was a notable lack of awareness regarding behaviors that embody national belonging. The results revealed statistically significant differences in awareness based on gender, favoring males, while no significant differences were observed concerning academic specialization, academic level, or social and economic status.